Towards industrial revolution (IR) 4.0 in the construction industry: Readiness of contractors - Zulkiflee Abdul-Samad; Lim Liang Xin; Wesam Salah Alaloul; Hafez Salleh (Results in Engineering, 2024)
Technologies and innovations have fuelled the growth of the construction industry, in line with the fourth industrial revolution (IR 4.0). Despite the fast development of IR 4.0 around the globe, hesitation remains among the construction industry towards its adoption. Therefore, this study aims to evaluate the readiness of contractors in the Malaysian construction industry towards IR 4.0, identify their level of understanding, and the current involvement of their organisations in driving this digital transformation. Questionnaires were distributed among contractors with varying job natures in the construction industry to investigate their advancement of current practices. Quantitative analysis was carried out to analyse statistical data collected from contractors to identify their organisation readiness level, and based on the specified parameters, the IR 4.0 readiness conceptual framework has been designed. The results reveal that the level of readiness of contractors towards IR 4.0 in Malaysia is moderate in terms of knowledge, technology, and operation management. The designed IR 4.0 conceptual framework can be adopted as a guideline by construction organisations or companies around the globe to assess the readiness level for IR 4.0 technologies.